First abundance estimates of Magellanic penguin (Spheniscus magellanicus) colony at Tucker Islet - Acevedo, Jorge; Moraga, Claudio A.; Gaete, Katherine; Aguilar, Constanza; Acevedo-Oyarzo, Ignacio; Ochoa-Sanchez, Manuel; Acuna, Paola (My University, 2024)
The nesting site of Magellanic penguins (Spheniscus magellanicus) at Tucker islets (54 degrees 09'S; 70 degrees 17'W), Chile, is documented and information from the first population abundance estimate on the largest islet during the beginning of chick rearing is provided. Ground-based counts yielded an estimate of 8883 (95% Confidence Intervals: 6653-11,802) burrows; however, counts of active burrows resulted in a total estimate of 2218 (95% Confidence Intervals: 1593-2840) breeding pairs. Based on the estimated total of burrows, this suggests a population decline consistent with trends for other colonies in the Magellan Strait and adjacent waters in Chile. An annual monitoring program to track population changes, breeding success, and chick and egg survival rates is required to assess the species' conservation status of the colony.
Keywords: census; demography; abundance; tierra del fuego; chile